Nanomagnetism in the environment - barbosa, d (2017)
Nanomagnetism was once seen as a utopia, and although its potential use was foreseen, there was no real observed development for a long time. All this changed, since the development of magnetic carriers and tagging technologies, as these techniques enable to manipulate de surface of the nanomagnetic particle, making possible to attach them to virtually any given substance, and therefore create agglomerates that we then may manipulate magnetically. Therefore, a huge effort has been put, in the last decade, to optimize the size and shape of these nanomagnetic particles, and many methods have been proposed and successfully implemented, among which we may stand out co-precipitation, hydrothermal, micro-emulsion, decomposition and pyrolisis. The applications are many and in the environmental area these nanomagnetic particles has been used effectively for water and waste water treatment, namely by effectively removing heavy metals and other important contaminants, for soil and underground water treatment, by the use of zero valent iron, in environmental catalytical degradation of contaminants, in environmental analytical chemistry, in greener alternative routes, etc. In this work will be reviewed the current status of the nanomagnetic particle applications in the environment, including regeneration of the particles and the final destination of the spent solutions.